Speaking Poverty Among Learners of English in Sierra Leone - John Pahoni Stevens; Abu Bakarr Sheriff (European Scientific Journal, ESJ, 2026)
The study examined sociocultural and linguistic strategies for cultivating ESL oral proficiency among Learners of English in Sierra Leone. It aimed to determine the relationship between learners’ bi/multilingual backgrounds and their English adeptness, as well as the influence of societal and cultural temperateness on language learning. A systematic random sampling technique was employed within a mixed-methods design, and data were collected from 1000 learners using questionnaires, discussions and interviews with results analyzed and presented. Findings showed that over 85% of the learners made noticeable pronunciation errors during speaking activities. The study also revealed that traditional teaching methods, such as grammar translation and rote learning, contributed significantly to the decline in fluency and overall language proficiency. Furthermore, learners in urban areas performed better than those in rural settings. Many learners demonstrated weaknesses in spelling, pronunciation, and subject-verb agreement in both spoken and written communication. These outcomes were linked to teacher centred, traditional teaching methods and exam oriented approaches that relied heavily on textbooks. The study recommended increased learner participation through interactive strategies such as open discussions, debates, peer and public speaking. From the perspective of Authenticity Theory, the findings indicated that oral fluency development depended not only on linguistic knowledge but also on meaningful, real life language use with focus on society and culture. Learners who engaged in authentic speaking activities showed greater confidence, improved enunciation, and enhanced ESL use. In contrast, fluency remained limited where instruction focused mainly on rote memorization and examination drills, highlighting a gap between academic achievement and communicative competence.